IMPROVING ACTIVITIES AND OUTCOMES OF VOLLEYBALL THROUGH APPLICATION OF PROBLEM BASED LEARNING MODELS IN CLASS VII STUDENTS OF SMP NEGERI 18 BANDA ACEH - Rahmaniah; Siti Mayang Sari; Akmaluddin; Lili Kasmini (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This research is a literature review that provides some information relatedto the phenomenon being discussed in this study. The purpose of this studywas to find out about character education as an effort to apply religious,moral and ethical values to students through science, with the assistance ofparents, teachers and the community, which is very important for theformation and development of students' character. This potential must behoned and socialized properly so that the character of each child is formedand develops optimally. Society in this digital era, children can easily enjoydigital media. The digital era has not only positive but also negative impacts.The role of teachers and parents is very important to guide and control whatchildren do with digital media so that children can make the best use of theopportunities that exist. digital media and get maximum benefits for bothyourself and your life. The results of the research can be applied to the worldof education by utilizing digital but with good direction and guidance fromteachers and parents.